Laparoscopy An Interdisciplinary Approach - Meinhold-Heerlein, Ivo (IntechOpen, 2011)
Over the last decades an enormous amount of technical advances was achieved in the field of laparoscopy. Many surgeons with surgical, urological, or gynaecological background have contributed to the improvement of this surgical approach which today has an important and fixed place in the daily routine. It is therefore comprehensible to compose a book entitled laparoscopy serving as a reference book for all three disciplines. Experts of each field have written informative chapters which give practical information about certain procedures, indication of surgery, complications and postoperative outcome. Wherever necessary, the appropriate chapter is illustrated by drawings or photographs. This book is advisable for both beginner and advanced surgeon and should find its place in the libraries of all specialties - surgery, urology, and gynecology.